Plant-induced insoluble Cd mobilization and Cd redistribution among different rice cultivars. (20th May 2020) - Li, Xinyang; Peng, Peiqin; Long, Jian; Dong, Xia; Jiang, Kai; Hou, Hongbo
Abstract: Selecting rice varieties that adsorb less or more Cd from soil can be respectively applied to safety rice production and phytoremediation. Considering plant-induced Cd mobilization will contribute to the rice cultivar screening. We firstly executed a pot experiment to assess the effect of rice plants on soil Cd forms (BCR method). The results showed that the presence of rice significantly reduced residual-Cd (BCR4) concentrations, indicating the rice plant-induced insoluble Cd mobilization. Subsequent sand culture trial with four rice species (conventional and hybrid low-Cd rice, conventional and hybrid high-Cd rice) and four insoluble Cd compounds (CdS, [Cd3 (PO3 )2 ], CdCO3 and CdSe) were conducted to further discuss the interaction between insoluble Cd among different rice varieties. The results showed that rice plants do solubilize soil Cd especially insoluble Cd form due to the interaction among rhizosphere acidification, root secretion of organic matter ligand and other ligands, like phytosiderophore. High-Cd cultivar and hybrid rice cultivar had a greater ability to solubilize the insoluble Cd. Visual MINTEQ predicted that free Cd 2+ (∼85.6%) were the dominant Cd speciation of mobilized Cd followed by Cd-DOM complexes (∼7.80%) and other ligand-complexes (∼6.51%) in the rhizosphere solution. Cd bound to protein and pectates and to undissolved phosphate were the major mobilized-Cd chemical forms in rice roots and shoots. In addition, the subcellular analysis suggested that half of mobilized-Cd precipitated in the cell wall of rice root and shoot and the other Cd entranced into the protoplast of rice cell. The fate of rice plant-induced insoluble Cd mobilization could be an indispensable factor in prospective phytoremediation and cleaner rice production. Graphical abstract: Image 1